(untitled) (Journal of Fiber Bioengineering and Informatics, 2010)
Polyaniline/Fe_3O_4 nanoparticle composite was prepared by microemulsion in-situ polymerizing aniline in the presence of Fe_3O_4 nanoparticles upon the use of ammonium persulfate(APS) as the initiator, hydrochloric acid(HCl) as intermingling acid, cetyltrimethylammonium bromide (CTAB) as emulsifying agent and normal butanol as auxiliary emulsifying agent. The results revealed that a core-shell structure composite was obtained successfully. Further more, pure PANI solution was not able to be electrospun into the fibrous structure, so electrospinning of emeraldine base Fe_3O_4-polyaniline/ polyacrylonitrile (Fe_3O_4-PANI/PAN) blends with different composition ratios were performed using N,N-Dimethylformamide as solvent. Morphology and fibers diameters were investigated by scanning electronic microscopy (SEM). The fibers with diameter ranging from 168 to 300 nm were obtained. The ratio of polyaniline/Fe_3O_4 to PAN was fixed at 3:8. Scanning electron microscopy indicated that the diameter of the composite nanofiber increased with the content of Fe_3O_4.